Survival and growth responses of Australian provenances of Eucalyptus tereticornis and Eucalyptus camaldulensis in soils of different salinities in North-West India - Dhanda, S.K.; Toky, O.P. (Indian Journal of Agroforestry, 2020)
Seeds of eight Australian provenances of Eucalyptus camaldulensis and Eucalyptus tereticornis, received from the CSIRO, Australia were tested on three saline soils (0.45, 2.16 and 3.97 dS m-1) in field conditions in Haryana located in north-west India. One local Indian seed source of Eucalyptus tereticornis was also included in the study for comparison. The growth of two years old plants varied significantly (P<0.05) among the provenances. The height of plants ranged from 210 to 447 cm, the collar diameter from 35 mm to 91 mm and dry weight from 1.98 kg to 3.41 kg/plant. Growth was adversely affected by the salinity. However, the root length of the plant increased significantly as the salinity levels arises indicating that more biomass was allocated to the underground parts under stress conditions. The maximum growth was attained by Eucalyptus camaldulensis of Emu Creek, Petford followed by Laura River, Qld and minimum inÂ Eucalyptus tereticornis (of Indian local source). Eucalyptus tereticornis NW Mt. Molloy, QLD (Australia) performed better as compared to Eucalyptus tereticornis (of Indian local source) in three levels of salinity. The results are important since eucalypts are preferred by the farmers on saline soils in north-west India.